2019
DOI: 10.1021/jacs.9b06521
|View full text |Cite
|
Sign up to set email alerts
|

The Photoaddition of a Psoralen to DNA Proceeds via the Triplet State

Abstract: Psoralens are natural compounds that serve in the light dependent treatment of certain skin diseases (PUVA therapy). They are DNA intercalators that upon photoexcitation form adducts with thymine bases. For one psoralen derivative, 4′-aminomethyl-4,5′,8-trimethylpsoralen (AMT), the photoreactions are characterized here by nanosecond UV–vis and IR absorption spectroscopy. The triplet state of AMT is identified as the reactive one. On the 1–10 μs time scale this local triplet state transforms into a triplet bira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 58 publications
(165 reference statements)
5
28
0
Order By: Relevance
“…Presumably, this is due to similar spectral signatures of the local triplet state and the triplet biradical. Such similarity was already observed for AMT and AT-DNA [23]. For this system, the intermediary of a triplet biradical found strong support from time-resolved IR spectroscopy.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Presumably, this is due to similar spectral signatures of the local triplet state and the triplet biradical. Such similarity was already observed for AMT and AT-DNA [23]. For this system, the intermediary of a triplet biradical found strong support from time-resolved IR spectroscopy.…”
Section: Discussionsupporting
confidence: 80%
“…Our previous results on the furan side photo-addition of AMT to AT-DNA [23] showed that this addition proceeds via the local triplet state of AMT and a triplet biradical. The present study indicates that this mechanism also applies to 8-MOP and TMP.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We cannot exclude that our substituents alter the spectrotemporal properties of psoralen and the quantum yield of DNA photoaddition (42). Diekmann et al have shown that photoaddition of intercalated AMT to thymine proceeds via the triplet state with quantum yield 0.12 (43). Though we have focused on intercalation efficiency as the basis for our molecules' efficacy, triplet quantum yields should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 96%